Mapping the global extent of malaria in 2005. - Guerra, C; Snow, R; Hay, S (2006)
Guidelines for travellers on malaria chemoprophylaxis, the altitude limits of dominant vector species, climate suitability for malaria transmission and human population density thresholds have been used to map the crude spatial limits of Plasmodium falciparum and Plasmodium vivax transmission on a global scale. These maps suggest that 2.510 and 2.596 billion people were at possible risk of transmission of P. falciparum and P. vivax, respectively, in 2005. Globally, 75 per cent of humans who are exposed to P. falciparum risk live in only ten countries.